Sulfur-containing amino acids and their metabolites in atrial fibrosis - Wang, Rui; Qi, Yong Fen; Ding, Chun Hua; Zhang, Da (Frontiers in Pharmacology, 2022)
Atrial fibrosis, a symbol of atrial structural remodelling, is a complex process involved in the occurrence and maintenance of atrial fibrillation (AF). Atrial fibrosis is regulated by multiple factors. Sulfur containing amino acids and their metabolites, such as hydrogen sulfide (H2S) and taurine, can inhibit the process of atrial fibrosis and alleviate atrial remodeling. However, homocysteine can promote the activation of atrial fibroblasts and further promote atrial fibrosis. In this review, we will focus on the recent progress in atrial structural changes and molecular mechanisms of atrial fibrosis, as well as the regulatory roles and possible mechanisms of sulfur containing amino acids and their metabolites in atrial fibrosis. It is expected to provide new ideas for clarifying the mechanism of atrial fibrosis and finding targets to inhibit the progress of atrial fibrosis.